RAS mutation testing in patients with metastatic colorectal cancer in French clinical practice: A status report in 2014. Issue 5 (May 2018) - Lièvre, Astrid; Merlin, Jean-Louis; Sabourin, Jean-Christophe; Artru, Pascal; Tong, Sabine; Libert, Lucie; Audhuy, François; Gicquel, Corinne; Moureau-Zabotto, Laurence; Ossendza, Roch-Anicet; Laurent-Puig, Pierre; Ducreux, Michel
Abstract: Background: RAS ( NRAS  +  KRAS ) mutation testing is required in addition to simple KRAS testing prior to initiating anti-epidermal-growth-factor-receptor (EGFR) antibodies (MAb) as in metastatic colorectal cancer (mCRC). Aims: To assess prescription and implementation rates of RAS/KRAS mutation testing. To describe the RAS/KRAS mutation test procedure and its impact on therapeutic strategy. Patients and methods: Observational retrospective study conducted from June to September 2014 in all consecutive patients with newly diagnosed mCRC. Results: Data from 375 patients (male: 57.8%; mean age, 65.7 ± 11.7 years) were analysed. RAS / KRAS mutation testing was prescribed in 90.1% of patients (338/375). The test was prescribed within 1 month around mCRC diagnosis and prior to first-line therapy in 73.1% (242/331) and 85.4% (280/328) of patients, respectively. Time from test request to receipt of results was 24.6 ± 17.2 days. 59.7% of patients (190/318) had a mutation, mainly KRAS (47.9%; 152/317). Anti-EGFR MAb was prescribed in 90.9% of RAS -wild-type cases (60/66), consistent with the goal of genotyping-testing in this population. Conclusion: In 2014, RAS genotyping-testing in addition to KRAS testing was routinely prescribed and performed in mCRC patients in France. Time to receive results remains long and must be reduced so as to match clinical practice.